Epitope specificity determines cross‐protection of a SIT‐induced IgG4 antibody. Issue 1 (30th September 2015) - Gadermaier, E.; James, L. K.; Shamji, M. H.; Blatt, K.; Fauland, K.; Zieglmayer, P.; Garmatiuk, T.; Focke‐Tejkl, M.; Villalba, M.; Beavil, R.; Keller, W.; Valent, P.; et al.
Abstract: Background: The calcium‐binding 2EF‐hand protein Phl p 7 from timothy grass pollen is a highly cross‐reactive pollen pan‐allergen that can induce severe clinical symptoms in allergic patients. Recently, a human monoclonal Phl p 7‐specific IgG4 antibody (mAb102.1F10) was isolated from a patient who had received grass pollen‐specific immunotherapy (SIT). Methods: We studied epitope specificity, cross‐reactivity, affinity and cross‐protection of mAb102.1F10 towards homologous calcium‐binding pollen allergens. Sequence comparisons and molecular modelling studies were performed with ClustalW and SPADE, respectively. Surface plasmon resonance measurements were made with purified recombinant allergens. Binding and cross‐reactivity of patients' IgE and mAb102.1F10 to calcium‐binding allergens and peptides thereof were studied with quantitative RAST‐based methods, in ELISA, basophil activation and IgE‐facilitated allergen presentation experiments. Results: Allergens from timothy grass (Phl p 7), alder (Aln g 4), birch (Bet v 4), turnip rape (Bra r 1), lamb's quarter (Che a 3) and olive (Ole e 3, Ole e 8) showed high sequence similarity and cross‐reacted with allergic patients' IgE. mAb102.1F10 bound the C‐terminal portion of Phl p 7 in a calcium‐dependent manner. It cross‐reacted with high affinity with Ole e 3, whereas binding and affinity to the other allergens were low. mAb102.1F10 showed limited cross‐inhibition of patients' IgE binding and basophil activation. Sequence comparison and surface exposure calculations identified three amino acids likely to be responsible for limited cross‐reactivity. Conclusions: Our results demonstrate that a small number of amino acid differences among cross‐reactive allergens can reduce the affinity of binding by a SIT‐induced IgG and thus limit cross‐protection.